SEROLOGICAL RESPONSES TO SARS-COV-2 VACCINATION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A PROSPECTIVE COHORT STUDY. (22nd January 2022) - Quan, Joshua; Ma, Christopher; Panaccione, Remo; Kanji, Jamil; Tipples, Graham; Sharifi, Nastaran; van Huyssteen, Michelle; Markovinovic, Ante; Turnbull, LeeAnn; Bindra, Gurmeet; Mahoney, Douglas; Ingram, Richard; et al.
Abstract: BACKGROUND: The immune response of SARS-CoV-2 vaccines is uncertain in those with Inflammatory Bowel Disease (IBD) due to a diverse array of immune-modifying therapies that vary in the mechanism of immunosuppression. AIM: We aimed to quantify the serological response to SARS-CoV-2 vaccines in those with IBD and determine antibody levels across varying therapeutic options. METHODS: Individuals with IBD who received first and/or second dose of a COVID-19 vaccine (Pfizer-BioNTech, Moderna, and/or AstraZeneca) were assessed for serological response (2–4 weeks after first dose; 2–8 weeks after second dose and 8–18 weeks after second dose) using the SARS-CoV-2 IgG II Quant assay to the spike protein of SARS-CoV-2. The cohort was stratified based on age, sex, vaccine received, IBD type, IBD therapeutic, and prior confirmed diagnosis of COVID-19. The primary outcome was seroconversion defined as IgG levels of ≥50 AU/mL. Secondarily, we evaluated the geometric mean titer (GMT) with 95% confidence intervals (CI). RESULTS: Table 1 describes the characteristics of individuals with IBD ( n =464) with serological data following the first dose ( n =266) and/or second dose ( n =303) of a COVID-19 vaccine. After the first dose of the vaccine, 81.6% seroconverted, with the lowest first-dose conversion rates in patients taking anti-TNF monotherapy (79.7%), anti-TNF combination therapy (52.9%), and corticosteroids (50.0%) (Table 1). Overall, 98.4% of the cohort seroconverted within 2–8 weeks of the second dose, with 94.6% seropositive within 8–18 weeks of the second dose. Seroconversion after second dose was consistently high across all medication classes (range: 94.6%–100.0%), except for oral corticosteroids (62.5%). GMT levels significantly increased (p<0.0001) from first dose (1679 AU/mL) to second dose at 2–8 week (7943 AU/mL) but fell significantly (<0.0001) to 3565 AU/mL 8–18 weeks from second dose (Table 1, Figure 1). GMT levels 2–8 weeks after second dose were higher in those with prior COVID-19 (12, 729 AU/mL), but lower in those receiving anti-TNF combination therapy (4231 AU/mL) and oral corticosteroids (5996 AU/mL) (Table 1). CONCLUSION: Seroconversion rates following full-regimen vaccination are high in patients with inflammatory bowel disease across all medication classes except for anti-TNF combination therapy and oral corticosteroids. Antibody titres and seroconversion rates tend to decrease after 8 weeks post-full vaccination, which is consistent across medication classes.